The impact of online customer review on purchase intention with trust as a mediating variable - Anjaya, Arisa; Dwita, Vidyarini (Universitas Negeri Padang, 2023)
This study aims to analyze how online customer reviews affect purchase intentions, with trust as a mediating variable at Optik Mekar Padang. The subjects of this study were people who had never purchased products from Optik Mekar in West Sumatra. The research participants totaled 230 respondents who were selected as samples. Data were collected through online questionnaire distribution as well as through direct interviews and then analyzed using SmartPLS software. The results of this study reveal that (1) online customer reviews have a significant positive impact on purchase intention, (2) online customer reviews have a significant positive effect on trust (3) trust has a significant positive effect on purchase intention (4) online customer reviews mediated by trust on purchase intention have a significant positive relationship, and trust can mediate the effect of online customer reviews on purchase intention.